Policy Communication on Twitter Social Media: Development of Sustainable Tourism Destinations in West Nusa Tenggara - Zitri, Ilham; Amil, Amil; Lestanata, Yudhi; Rahmat, Al Fauzi (Journal Public Policy, 2024)
This research explains Policy Communication on Twitter Social Media: Development of Sustainable Tourism Destinations in NTB Province. New media offers digitization, convergence, interaction, and development of networks related to creating and delivering messages. Digital media is a source of information and a platform for tourists or visitors to communicate. Digital technology has experienced significant growth. This study aims to identify policy communication for Sustainable Tourism Destination Development through social media communication tools. NTB Provincial Government Twitter Account @ntb_Prov and Personal Twitter Account @bangzul_ntb. This research uses a qualitative method with the Qualitative Data Analysis (QDA) Miner approach, used for content, network, and cloud analysis using Nvivo 12 Plus software. The findings show that the intensity of each account has provided an overview of how local governments disseminate information related to the policies they produce. The total tweet intensity and highest tweet intensity were made by the @ntb_Prov account, with quite a significant difference compared to the @bangzul_ntb account. In analyzing the information content shared regarding the theme of Sustainable Tourism Destination Development, each account has distributed information directly related to the Sustainable Tourism Destination Development policy. Policy communication on Twitter is also a means of gathering input and responses from the public regarding the development of sustainable tourism destinations in West Nusa Tenggara. Overall, policy communication on Twitter and social media regarding the development of sustainable tourism destinations in West Nusa Tenggara is an effort to increase public awareness and participation in sustainable tourism development in the region.